In Memoriam: Jimmie C. Holland, M.D., and James F. Holland, M.D. - Bertagnolli, Monica M. (Oncologist, 2018)
Reflections on the legacies of Drs. James and Jimmie Holland, who became the most impactful couple in oncology as one worked to save lives by developing new therapies and the other worked to ensure the quality of the lives lengthened and saved.